(untitled) (Research, Society and Development, 2021)
The aim of this study was to analyze the trend and epidemiological profile of mortality from external causes in the state of São Paulo, from 2000 to 2018. Ecological time series study, with data on deaths from external causes (chapter XX ICD 10) extracted from the Mortality Information System. Age, sex, race, education, type of death and place of occurrence were investigated. Variations in mortality from external causes were verified using standardized mortality rates by sex/age group, and simple linear regression models were estimated for rates per year. To analyze whether the rate of deaths differed between the investigated variables, the chi-square test was used, significance level of 5%. During the study period, there were 506.374 deaths from external causes in the state, with a significant decrease over the years, an overall rate of 90.61/100.000 inhabitants (2000) to 50.21/100.000 inhabitants (2018). The decrease was observed in all age groups, in both sexes, except for the elderly, being more expressive in males, 15 to 29 years old (258.82/100.000 inhabitants 2000 to 83.65/100.000 inhabitants 2018). White population concentrated the majority of deaths (81.1% total), there was an increase in the rate of deaths for people with 8 years of schooling or more and for widowed/divorced people. Falls, land transport accidents, accidental risks to breathing and suicide have increased proportionately, and homicides have declined over the years. Most deaths occurred in hospitals. It is necessary to know the trend and distribution of mortality from external causes in order to better guide Public Policies.